2017
DOI: 10.1002/bab.1613
|View full text |Cite
|
Sign up to set email alerts
|

Working at the membrane interface: Ligand‐induced changes in dynamic conformation and oligomeric structure in human aromatase

Abstract: Aromatase catalyzes the biosynthesis of estrogens from androgens. Owing to the physiological importance of this conversion of lipophilic substrates, the interaction with the lipid bilayer for this cytochrome P450 is crucial for its dynamics that must allow an easy access to substrates and inhibitors. Here, the aromatase-anastrozole interaction is studied by combining computational methods to identify possible access/egress routes with the protein inserted in the membrane and experimental tools aimed at the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…In addition to function in a soluble form, CYPs are able to attach to membrane with its N-terminal, and interact with its redox partner CYP reductase in the membrane environment, which are essential for electron transfer in the catalytic cycle 51 . Interactions with membrane have been observed to modulate the conformational dynamics of human aromatase (CYP19A1) and alter the substrate/inhibitor access channels 52 . Computational simulations and experimental data have also revealed that interactions of CYP enzymes with partner reductase in the membrane could affect the substrate binding 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to function in a soluble form, CYPs are able to attach to membrane with its N-terminal, and interact with its redox partner CYP reductase in the membrane environment, which are essential for electron transfer in the catalytic cycle 51 . Interactions with membrane have been observed to modulate the conformational dynamics of human aromatase (CYP19A1) and alter the substrate/inhibitor access channels 52 . Computational simulations and experimental data have also revealed that interactions of CYP enzymes with partner reductase in the membrane could affect the substrate binding 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…CYP19A1 activity is also inhibited by bisphenol A and sildenafil [55]. CYP19A1 inhibitors like anastrozole are used in the treatment of breast cancer and to treat the excess production of estrogen in men [57].…”
mentioning
confidence: 99%
“…A topological characterization of the aromatase structure has been attempted using the available crystallographic model of substrate-containing aromatase (PDB code 4kq8), and an in silico version of the ligand-free protein, obtained through a molecular dynamics simulation [25]. A contact network approach consists of a coarse-graining algorithm that reduces the amino acids of a protein into "nodes" of a tridimensional grid, identifying the position of each residue with that of its α-carbon.…”
Section: Contact Network Analysismentioning
confidence: 99%